Annunciations Sacred Music for the Twenty-First Century - Corbett, George (Open Book Publishers, 2019)
"Our contemporary culture is communicating ever-increasingly through the visual, through film, and through music. This makes it ever more urgent for theologians to explore the resources of art for enriching our understanding and experience of the Judeo-Christian tradition. Annunciations: Sacred Music for the twenty-First Century, edited by George Corbett, answers this need, evaluating the relationship between the sacred and the composition, performance, and appreciation of music. Through the theme of 'annunciations', this volume interrogates how, when, why, through and to whom God communicates in the Old and New Testaments. In doing so, it tackles the intimate relationship between Scriptural reflection and musical practice in the past, its present condition, and what the future might hold. Annunciations comprises three parts. Part I sets out flexible theological and compositional frameworks for a constructive relationship between the sacred and music. Part II presents the reflections of theologians and composers involved in collaborating on new pieces of sacred choral music, alongside the six new scores and links to the recordings. Part III considers the reality of programming and performing sacred works today. This volume provides an indispensable resource for scholars and artists working at the interface between theology and the arts, and for those involved in sacred music. However, it will also be of interest to anyone concerned with the ways in which the Divine communicates through word and artistry to humanity."